Arteriovenous grafts: early ultrasonography tells their fortune - Kudlicka, Jaroslav; Malik, Jan; Tuka, Vladimir; Chytilova, Eva; Krupickova, Zdislava; Grauova, Barbora; Vorcakova, Jaroslava; Janak, David; Kavan, Jan; Kittnar, Otomar; Slavikova, Marcela (American journal of nephrology, 2015)
BACKGROUND: The patency of arteriovenous grafts (AVG) for hemodialysis is mostly limited by growing stenoses that lead to decreasing of blood flow, thromboses and finally to access failure. The aim of this study was to find out if detection of any pathology by duplex Doppler ultrasonography (DDU) early after creation of AVG could identify those with lower survival. METHODS: We retrospectively enrolled AVG examined by DDU in our center within 40 days after their creation during the last 10 years. The findings were divided into 4 subgroups: (1a) normal finding, (1b) DDU risk factor (low flow volume, medial calcinosis of the feeding artery, presence of intimal hyperplasia in the venous anastomosis), (2a) non-significant or (2b) significant stenosis. The primary outcome measure was the cumulative survival of people with AVGs, and the secondary was the primary (unassisted) survival. All patients underwent DDU surveillance every 3 months with pre-emptive treatment of significant stenoses. RESULTS: Overall, 340 cases were found; the median follow-up was 565 days. Normal DDU finding had 60% cases, DDU risk factor 18% cases, non-significant stenosis 13% cases and significant stenosis 9% cases. Occurrence of early significant stenosis was associated with high risk of access loss (hazards ratio (HR) 14.73; 95% CI 5.10-42.58; p < 0.0001). Similarly, the presence of a DDU risk factor and of a non-significant stenosis were related to significantly shorter access lifespan (HR 2.86; 95% CI 1.10-7.40; p = 0.03 and HR 2.83; 95% CI 1.12-7.17; p = 0.03, respectively). CONCLUSION: DDU examination of AVG early after their creation can identify those at higher risk and may contribute to individualize the surveillance strategy.
Keywords: Young Adult; cévní protézy; duplexní dopplerovská ultrasonografie; Male; kohortové studie; retrospektivní studie; okluze cévního štěpu; Vascular Calcification; Risk Factors; Kidney Failure, Chronic; mladý dospělý; Cohort Studies; Ultrasonography, Doppler, Duplex; chronické selhání ledvin; Adolescent; polytetrafluoroethylen; dialýza ledvin; Adult; Blood Vessel Prosthesis Implantation; Aged; dospělí; mužské pohlaví; senioři; Arteriovenous Shunt, Surgical; mladiství; arteriovenózní zkrat; Blood Vessel Prosthesis; Renal Dialysis; senioři nad 80 let; Graft Occlusion, Vascular; lidé; ženské pohlaví; Polytetrafluoroethylene; Humans; rizikové faktory; Aged, 80 and over; vaskulární kalcifikace; cévy - implantace protéz; neointima; Retrospective Studies; Female; lidé středního věku; Neointima; Middle Aged